Konstruksi Pengetahuan Penyelamatan dan Evakuasi Korban Laka Laut pada Komunitas SAR Rimba Laut di Payangan - Destianah, Luky; Mulyono, Joko (Huma: Jurnal Sosiologi, 2024)
The existence of SAR Rimba Laut as rescue volunteers equipped with qualified knowledge and skills is needed to minimise the occurrence of marine accidents, considering that the waters of Jember Regency have a high risk caused by several factors. This study aims to determine the construction of knowledge of rescue and evacuation of victims of marine accidents in the SAR Rimba Laut community in Payangan. This study used a qualitative research method with a phenomenological approach. The research subjects consisted of nine people who were divided into two categories, namely primary informants and secondary informants. The data collection process was carried out by means of observation, interviews, and documentation. Data validity techniques used triangulation techniques. While the data analysis technique uses an interactive model, which consists of data collection, data reduction, data presentation, and conclusion drawing. The process of knowledge production related to rescue and evacuation in Rimba Laut SAR is described through three important moments, namely externalisation, objectivation, and internalisation that run simultaneously. Externalisation is reflected in the knowledge production process of Rimba Laut SAR related to rescue and evacuation. In objectivation, SAR Rimba Laut begins to take on roles and immerse itself in humanitarian actions. The externalisation and objectivation phases are then absorbed and reinterpreted within each individual which is referred to as internalisation. It is important for the government to implement training and provide facilities related to the rescue and evacuation of victims of marine accidents.